2011
DOI: 10.1002/anie.201100265
|View full text |Cite
|
Sign up to set email alerts
|

Tracking N‐Acetyllactosamine on Cell‐Surface Glycans In Vivo

Abstract: In living color: Many mammalian glycans associated with signaling receptors contain terminal or penultimate N‐acetyllactosamine. A highly specific method for labeling this disaccharide on cell‐surface glycoproteins of live cultured cells and zebrafish embryos is reported. The two‐step chemoenzymatic approach involves in situ fucosylation followed by a bioorthogonal click reaction (see scheme; α(1,3)FucT=α(1,3)‐fucosyltransferase).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(60 citation statements)
references
References 24 publications
1
58
0
Order By: Relevance
“…Interestingly, the periarteriolar lymphoid sheaths (PALS) of the white pulp of the spleen, where naïve T cells reside, had lower LacNAc expression (Figure 4, Figure S7). This result is consistent with our previous findings, obtained by flow cytometry, which show that activated T cells bear higher levels of LacNAc as compared to their naïve counterparts [25] . This pattern, however, was not distinguishable using the direct labeling method.…”
supporting
confidence: 94%
“…Interestingly, the periarteriolar lymphoid sheaths (PALS) of the white pulp of the spleen, where naïve T cells reside, had lower LacNAc expression (Figure 4, Figure S7). This result is consistent with our previous findings, obtained by flow cytometry, which show that activated T cells bear higher levels of LacNAc as compared to their naïve counterparts [25] . This pattern, however, was not distinguishable using the direct labeling method.…”
supporting
confidence: 94%
“…S2A). Fucose modification can also be achieved by directly adding fucose using in vitro fucosylation assays (Zheng et al, 2011)(Fig. S2A).…”
Section: Resultsmentioning
confidence: 99%
“…To control for potential differential responses between cell lines, we performed in vitro fucosylation assays as described (Zheng et al, 2011). Since both CHO and LEC30 lines have endogenous Wnt activity, we normalized all data to untreated CHO or LEC30 lines, which we set as 100%.…”
Section: Methodsmentioning
confidence: 99%
“…[18] Furthermore, it has been shown that GDP-6-azidofucose is readily accepted by a recombinant H. pylori a(1,3)-fucosyltransferase, and this has been successfully employed to image glycans in the enveloping layer of zebrafish embryos. [19] The attraction of enzymatic labeling is that it affords near quantitative labeling, does not perturb signaling pathways, and is amenable to all cell types.…”
mentioning
confidence: 99%